Physiological regulation and efficient xylem water transport regulate diurnal water and carbon balances of tropical lianas - Chen, Ya-Jun (2017)
Tropical lianas deploy most of their leaves towards the top of the forest canopy, whereas trees exhibit a more stratified crown. Forest canopies are often exposed to hot and windy conditions, and how lianas cope with the extremely high transpirational demands under these environments remains unknown. We investigated stem hydraulic properties, leaf drought tolerance, diurnal changes in leaf and stem water potentials (Ψleaf and Ψstem), stomatal conductance (gs), photosynthetic rate, sap flow and stem native percentage loss of conductivity (PLC) for four liana species in a tropical forest in southwest China. Five co-occurring tree species were also selected for comparison. Lianas reached maximal transpiration at a relatively lower vapour pressure deficit (<1 kPa) than did co-occurring trees, suggesting vigorous photosynthesis during the morning. However, liana gs declined markedly over the day, with low gs at midday and afternoon. Lianas generally had higher stem sapwood-specific conductivity and maximum sap flux density but were less tolerant to drought-induced cavitation than were evergreen trees. Both lianas and trees lost leaf turgor in the top canopy at midday, but lianas lost leaf turgor earlier (∼2 h) than trees. Seven of eight species exhibited midday increases in PLC when xylem tensions were released to −0·3 to −0·5 MPa for PLC measurements. On average, lianas experienced high PLC (35·9%), along with a greater degree of disequilibrium between leaf and stem water potentials than trees (ΔΨstem–leaf: 1·37 MPa vs. 0·75 MPa) during the day. Earlier stomatal closure and efficient water transport may help lianas maintain higher Ψstem than trees despite having similar Ψleaf. Our results provide evidence that physiological regulation and efficient water transport mediate daily water relations in tropical lianas and may explain how lianas operate efficiently in tropical seasonal forests. Further studies involving a broader range of species are needed to confirm our findings.